Simulation of micro-injection molding - Ali, Mohammad Yeakub; Hung, N. P.; Yuan, S. (2000)
Two challenges in micro-injection molding process were the modification of conventional injection molding machine and simulation of the molding process. This paper simulates the micro-injection molding process using a conventional software. Successful simulation was performed for the micro-injection molding of polycarbonate micro-components with sub-millimeter dimensions. The micro-cavities, keeping along with a macro-cavity, were filled completely under non-variothermal process conditions. The percentage weight of the melt flow and average flow length were found proportional to the filling time. A sudden drop of melt temperature and a high concentration of shear stress were observed at the entrances of all micro-cavities. The melt flow velocity inside the micro-cavity was much lower than any other places of the cavity. Air traps were identified in each of the micro-cavities.